2018
DOI: 10.1016/j.neulet.2017.12.051
|View full text |Cite
|
Sign up to set email alerts
|

The Sonic Hedgehog signaling pathway regulates inferior alveolar nerve regeneration

Abstract: Activation of Shh signaling is known to be observed following injury of the peripheral nerves such as the sciatic nerve. However, the precise role of Shh signaling during peripheral nerve regeneration is not fully understood. The inferior alveolar nerve (IAN) is most commonly injured during oral surgery. Unlike the sciatic nerve, the IAN is isolated from other craniofacial tissues, as it resides in a long bony canal within the mandible. The IAN is thus an excellent experimental model for investigating peripher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 31 publications
2
32
0
1
Order By: Relevance
“…The AXONO module was enriched for the Hedgehog signaling pathway and the Estrogen signaling pathway. Sonic hedgehog (Shh) is essential for central nervous system development and is expressed within injured sciatic nerve 56 . Recently, reduced Shh signaling was shown to disturb axon regeneration via misregulated myelin degradation 56 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AXONO module was enriched for the Hedgehog signaling pathway and the Estrogen signaling pathway. Sonic hedgehog (Shh) is essential for central nervous system development and is expressed within injured sciatic nerve 56 . Recently, reduced Shh signaling was shown to disturb axon regeneration via misregulated myelin degradation 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Sonic hedgehog (Shh) is essential for central nervous system development and is expressed within injured sciatic nerve 56 . Recently, reduced Shh signaling was shown to disturb axon regeneration via misregulated myelin degradation 56 . Estrogen signaling has also been implicated in axon regeneration by accelerating peripheral nerve regeneration and increasing motoneuron participation 57,58 .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, as advancements and achievements in mesenchymal stem cell (MSC) research are developing rapidly, the use of MSCs to alleviate peripheral nerve injury has drawn researchers’ attention. Studies have reported that both adipose tissue-derived stem cells and bone marrow-derived stem cells are able to differentiate into neural-like cells and finally demonstrate a great inclination to nerve repair and regeneration in vivo [ 5 - 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…5,[91][92][93][94][95] There have been no specific reports illustrating the usage of dental stem cells in IAN injury repair by far. IAN injury mainly happens during mandibular fracture or oral surgery such as the third molar extraction and results in unpleasant complications including dysesthesia, allodynia and hyperalgesia.…”
Section: Inferior Alveolar Nerve Injurymentioning
confidence: 99%